Food Recall Protecs Consumers from Consuming Hazardous Meat and Poultry Products : A Review on 1995-1999 Recall Cases from FSIS-USDA - Sri Raharjo (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2001)
A recall is intended to remove meat or poultry from commerce when there is reason to believe that it may be injurious to helath, unfit for human consumption, adulterated, or incorrect labeling. The objective of this study was to evaluate Recall Cases during the period of 1995-199 as reported by the USDA-FSIS. During the period of 1995-1999, there were approximately 197 cases of recall were identified which consisted of 85% categorized as Class 1 and remaining 15% as Class II. More than 50% of the recall were warranted due to the pathogenic bacteria contamination and only a small proportions were due to the presence of extraneous material, drug residues, inadequate processing, and incorrect labeling. At least 80% of the bacterial contamination were associated with L. monocytogenes and E.coli O157:H7. On the average more than 2 million pounds of defective or hazardous meat products were withdrawn from commerce and some of the recall resulted 100% product recovery. This suggests that the firms respond positively to the program and as a result consumer's safety can be enhanced.